Ai-Driven Predictive Analytics n the Metaverse Era: Forecasting Halal Consumption Trends within the Framework of Islamic Marketing - Sibral Malasyi; Dwi Vita Lestari Soehardi; Yusrizal Yusrizal (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This paper examines the integration of Artificial Intelligence (AI)-based predictive analytics and Metaverse in predicting halal consumption trends within the ethical and spiritual framework of Islamic marketing. The primary research question explores how AI-based predictive analytics can predict halal market trends while remaining aligned with Sharia principles and consumer trust. The novelty of this study lies in the integration of AI and immersive technology as an ethical tool to advance the global halal economy. Using a qualitative systematic literature review of Scopus-indexed publications from 2019 to 2025 (k = approximately 45 articles), the findings indicate that AI improves the accuracy of halal market predictions through big data processing, sentiment analysis, and digital consumer behavior modeling. Meanwhile, Metaverse introduces an immersive virtual environment that encourages halal engagement through blockchain-based certification and an interactive marketplace. Data synthesis revealed that young Muslim consumers prioritize an